1992
DOI: 10.1038/357589a0
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity between sperm surface β-l,4-galactosyl-transferase and egg-coat ZP3 mediates sperm–egg binding

Abstract: Despite its importance, the molecular basis of mammalian gamete recognition has remained unclear. The enzyme beta-1,4-galactosyltransferase (Gal-transferase) has been viewed traditionally as a biosynthetic component of the Golgi complex, but is also found on the surface of many cells where it can bind its specific glycoside substrate on adjacent cell surfaces or in the extracellular matrix. In mouse it has been suggested that Gal-transferase on the sperm head mediates fertilization by binding oligosaccharide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
285
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(297 citation statements)
references
References 37 publications
9
285
2
Order By: Relevance
“…There is compelling evidence that carbohydratebinding proteins on the sperm surface mediate gamete recognition of different species by binding with high affinity and specificity to complex glycoconjugates on the zona pellucida (14 -16, 19, 34), including human (16,19,35,36). In the past two decades, the presence of several carbohydrate-binding proteins, such as galactosyltransferase (37), fucosyltransferase (38), ␣-mannosidase (39, 40), fucose-binding protein (41), selectin-like molecules (42), ␤-hexosaminidase (43), FA-1 (44), and others, on the sperm plasma membrane and their complementary sugar molecules on the zona pellucida have been suggested to be involved in sperm-egg interaction.…”
Section: Discussionmentioning
confidence: 99%
“…There is compelling evidence that carbohydratebinding proteins on the sperm surface mediate gamete recognition of different species by binding with high affinity and specificity to complex glycoconjugates on the zona pellucida (14 -16, 19, 34), including human (16,19,35,36). In the past two decades, the presence of several carbohydrate-binding proteins, such as galactosyltransferase (37), fucosyltransferase (38), ␣-mannosidase (39, 40), fucose-binding protein (41), selectin-like molecules (42), ␤-hexosaminidase (43), FA-1 (44), and others, on the sperm plasma membrane and their complementary sugar molecules on the zona pellucida have been suggested to be involved in sperm-egg interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we tried to isolate three glycopeptides, having bohydrate chains of ZPC [1,7]. However, carbohydrate strucone Asn residue, to which the intact carbohydrate chain is …”
mentioning
confidence: 99%
“…When N-acetyllactosamine repeats in the non-reducing regions of carbohydrate chains of removed in the secretory pathway, and mature ZPB consists of 330 amino acid residues [9]. Recently, we have reported that the ZPB and ZPC are removed by digestion with endo-β-galactosidase, they become separable by reverse-phase HPLC [5].N-terminal fragment (amino acid residues 137Ϫ247) obtained by lysyl endopeptidase digestion of endo-β-galactosidaseϪdi-In mice, sperm bind to A-galactose residues and/or β-N-acetylglucosamine residues at the non-reducing end of O-linked car-gested ZPB inhibits sperm-egg binding [10].In this study, we tried to isolate three glycopeptides, having bohydrate chains of ZPC [1,7]. However, carbohydrate strucone Asn residue, to which the intact carbohydrate chain is …”
mentioning
confidence: 99%
“…This oligosaccharide sequence has been reported as a major contributing element for human sperm‐oocyte binding 22, 23. There are also components on the sperm membrane reported as docking units, including the β1–4 galactosyltransferase 1 (B4GAL‐T1) peripheral protein, which plays a crucial role in human sperm‐oocyte binding 24, 25, 26, 27, 28, 29. To understand the dynamics of SLeX binding to sperm surface, we used B4GAL‐T1 as a model docking/binding unit on the sperm membrane and computed a molecular docking simulation to discover the locations and energetics of binding ( Figure   2 ).…”
Section: Resultsmentioning
confidence: 99%